2013
DOI: 10.1186/1471-2296-14-143
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to the prevention of overweight and obesity in the context of child health care in Sweden

Abstract: BackgroundOverweight and obesity in younger children could better be brought in focus through a deeper understanding of how Child Health Care nurses (CHC-nurses) perceive their work with the problems of overweight at the CHC Centers. The aim of this study was to elucidate the CHC-nurses conceptions of their preventive work with childhood overweight and obesity in Child Health Care.MethodA qualitative study, based on open-ended interviews, involving 18 CHC-nurses strategically selected from 17 CHC Centres in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 20 publications
3
58
0
8
Order By: Relevance
“…While recent studies suggest increased provider comfort in screening and counseling for obesity [27, 28], rates of obesity prevention and treatment activities in primary care remain low in many countries, including the USA Israel, Australia, and several European countries [25, 29, 30•, 3134]. Furthermore, primary care providers have expressed reservations about the effectiveness of provider-delivered obesity prevention and treatment strategies, citing concerns regarding the obesogenic environment, lack of parent motivation to make weight-related behavioral changes for themselves and their family, and low parent concern about child weight [16, 20, 22, 24, 27, 32, 3436]. …”
Section: Introductionmentioning
confidence: 99%
“…While recent studies suggest increased provider comfort in screening and counseling for obesity [27, 28], rates of obesity prevention and treatment activities in primary care remain low in many countries, including the USA Israel, Australia, and several European countries [25, 29, 30•, 3134]. Furthermore, primary care providers have expressed reservations about the effectiveness of provider-delivered obesity prevention and treatment strategies, citing concerns regarding the obesogenic environment, lack of parent motivation to make weight-related behavioral changes for themselves and their family, and low parent concern about child weight [16, 20, 22, 24, 27, 32, 3436]. …”
Section: Introductionmentioning
confidence: 99%
“…Among the barriers, the nurses highlighted lack of uniformity in obesity prevention and control guidelines, as well as inadequate management of the services. They also noted the need for knowledge about this chronic disease, responsibility, and cooperation among health team members (15) .…”
Section: Theme II -Perception Of Primary Health Care Nurses In Relatimentioning
confidence: 99%
“…Some of the studies reviewed mentioned that health team professionals had limited knowledge about obesity (15,17,(21)(22)37) . Research in Australia found that nurses were interested in participating in training aimed at child obesity prevention (17) .…”
Section: Theme II -Perception Of Primary Health Care Nurses In Relatimentioning
confidence: 99%
“…Possuir conhecimentos limitados sobre obesidade foi um tema destacado pelos enfermeiros nas pesquisas encontradas sobre a percepção desse profissional acerca de sua atuação frente à obesidade na APS (Isma et al, 2013;Blackburn et al, 2015). Ressalta-se que a falta de capacitação da equipe pode ser um dificultador no acolhimento às pessoas com obesidade, uma vez que é imprescindível que os profissionais de saúde da UBS estejam aptos e sensibilizados para captação e acolhimento eficientes dessa demanda (Brasil, 2014b (Minayo, 2015).…”
Section: Contextualizaçãounclassified
“…Em um município da região sudeste do Brasil, uma investigação que utilizou a antropometria na APS para o diagnóstico e acompanhamento do crescimento de crianças e adolescentes em parceria com o Nasf apontou que a ação realizada com 200 participantes, proporcionou a sensibilização dos pais ou responsáveis quanto à prevenção de agravos à saúde, levando-os a refletir sobre seus hábitos alimentares (Rosa, Sales, Andrade, 2017 (Matos et al, 2015). Também estudo realizado com 18 enfermeiros de APS na Suécia apontou que a deficiência de recursos físicos e a desorganização do serviço de saúde limitavam os participantes em sua atuação na prevenção do sobrepeso e obesidade infantil, resultando na concepção de que esta é uma tarefa difícil de ser desenvolvida pelos profissionais nesse nível de atenção à saúde (Isma et al, 2013).…”
Section: Quadro 1 -unclassified